1990
DOI: 10.1002/ccd.1810190203
|View full text |Cite
|
Sign up to set email alerts
|

Coronary angioplasty–unstable lesions and prolonged balloon inflation time

Abstract: One of the most important complications after percutaneous transluminal coronary angioplasty is the abrupt closure of the dilated vessel (unstable lesion). The treatment of choice for this complication is a new dilation, but unfortunately many of these cases require immediate surgery to avoid an acute myocardial infarction. Prolonged balloon inflations have been suggested to control this kind of complication. In order to discover the effect of prolonged inflations on the incidence of unstable lesions we studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 19 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…When angioplasty was first introduced in the last twentieth century, early randomized trials revealed immediate benefit of prolonged balloon inflation, although the sustainability of the patency benefit is conflicting [810]. However, the immediate benefit of prolonged angioplasty has not been consistently reported in randomized trials [11].…”
Section: Introductionmentioning
confidence: 99%
“…When angioplasty was first introduced in the last twentieth century, early randomized trials revealed immediate benefit of prolonged balloon inflation, although the sustainability of the patency benefit is conflicting [810]. However, the immediate benefit of prolonged angioplasty has not been consistently reported in randomized trials [11].…”
Section: Introductionmentioning
confidence: 99%